Asher Reich : portrait of a Hebrew poet - Mazor, Yair, 1950- (University of Wisconsin Press, 2003)
"Asher Reich's poetry has been characterized as vivid, vibrant, passionate, and expressionistic. Dominated by themes of stormy sensuality and frank sexuality, his dramatic imagery and metaphors interweave Mishnaic, Talmudic, and Biblical references in a colorful, complex poetic texture. The beautiful simplicity of Kovner's drawings - depicting female figures and natural landscapes - resonates throughout the book. Tender, stark, and striking, the drawings illustrate life's fragility and grace with a subtlety and dignity that complements Reich's sensitive style."--Jacket